Characterization of gyrA and gyrB mutations and fluoroquinolone resistance in Mycobacterium tuberculosis clinical isolates from Hubei Province, China - Chen,Jun (2012)
OBJECTIVE: The study aimed to investigate gyrA and gyrB mutations in Mycobacterium tuberculosis (MTB) clinical strains from 93 patients with pulmonary tuberculosis in Hubei Province, China, and analyze the association between mutation patterns of the genes and ofloxacin resistance level. RESULTS: Among 93 MTB clinical isolates, 61 were ofloxacin-resistant by the proportion method, and 32 were ofloxacin-susceptible MDR-TB. No mutation in the gyrB gene was found in any MTB strains. In the 61 ofloxacin-resistant isolates, 54 mutations were observed in the gyrA gene. Only one mutation in the gyrA gene was found in ofloxacin-susceptible MDR-TB isolates. In this study, the mutation patterns of gyrA involved seven patterns of single codon mutation (A90V, S91P, S91T, D94N, D94Y, D94G or D94A) and two patterns of double codons mutation (S91P & D94H, S91P & D94A). The ofloxacin minimal inhibitory concentrations (MICs) of three patterns of single codon mutations in the gyrA gene (codons 94, 90 and 91) showed a statistically significant difference (p < 0.0001). CONCLUSIONS: The gyrA mutations at codons 90, 91 and 94 constitute the primary mechanism of fluoroquinolone resistance in MTB, and mutations at codon 91 in the gyrA gene may be associated with low-level resistance to ofloxacin.